Synthesis of Some 3d Metal Complexes of Quinine and their Toxicological Studies - Tella, Adedibu C.; Obaleya, Joshua A. (Journal of Nepal Chemical Society, 2010)
Four metal complexes of antimalarials cinchona alkaloids; [Co(Quin)Cl3]-1, [Fe(Quin)Cl2H2O]SO3H2O-2, [Cu(Quin)ClSO4]∞-3 and [Cd(Quin)ClSO4]∞-4 have been synthesized and characterized by elemental analysis, conductivity, magnetic moment, IR, UV-Vis and mass spectroscopic techniques. The tetrahedral geometry is assigned for all the four complexes and the quinine ligand is protonated at quinuclidine N atom with the coordination of the metal at quinoline N atom for all the complexes. Complexes 1 and 2 have zwitterionic structures while complexes 3 and 4 are polymeric in nature with zig-zag extended chains (MCl- O -SO2- O -MCl- O –SO2—). Stability constant of the complexes were evaluated for the metal salts. The value of the stability constant (β) was found to be log 10.48, 9.92, 7.98 and 7.81 for Cu(II), Fe(III), Co(II) and Cd(II), respectively and the order of β was found to be Cu(II)>Fe(III)>Co(II)>Cd(II). The stability constant data revealed that concomitantly administration of quinine with preparation containing these metals may reduce their efficacy. Toxicological study was carried out by investigating the effect of administration of the complexes on alkaline phosphatase activity of kidney, liver and serum of Albino rats. All the examined four metal complexes were found to be non-toxic. Keywords: Quinine, stability constant, FTIR, MS, phosphates activity. DOI: 10.3126/jncs.v25i0.3280 Journal of Nepal Chemical Society Volume 25, 2010 pp 19-28